Magnetite as a provenance and exploration tool for metamorphosed base-metal sulfide deposits in the Stollberg ore field, Bergslagen, Sweden. (25th June 2022) - Frank, Katherine S.; Spry, Paul G.; O'Brien, Joshua J.; Koenig, Alan; Allen, Rodney L.; Jansson, Nils
Abstract: Magnetite is a common mineral in the Paleoproterozoic Stollberg Zn–Pb–Ag plus magnetite ore field (~6.6 Mt of production), which occurs in 1.9 Ga metamorphosed felsic and mafic rocks. Mineralisation at Stollberg consists of magnetite bodies and massive to semi-massive sphalerite–galena and pyrrhotite (with subordinate pyrite, chalcopyrite, arsenopyrite and magnetite) hosted by metavolcanic rocks and skarn. Magnetite occurs in sulfides, skarn, amphibolite and altered metamorphosed rhyolitic ash–siltstone that consists of garnet–biotite, quartz–garnet–pyroxene, gedrite–albite, and sericitic rocks. Magnetite probably formed from hydrothermal ore-bearing fluids (~250–400°C) that replaced limestone and rhyolitic ash–siltstone, and subsequently recrystallised during metamorphism. The composition of magnetite from these rock types was measured using electron microprobe analysis and LA–ICP–MS. Utilisation of discrimination plots (Ca+Al+Mn vs . Ti+V, Ni/(Cr+Mn) vs . Ti+V, and trace-element variation diagrams (median concentration of Mg, Al, Ti, V, Co, Mn, Zn and Ga) suggest that the composition of magnetite in sulfides from the Stollberg ore field more closely resembles that from skarns found elsewhere rather than previously published compositions of magnetite in metamorphosed volcanogenic massive sulfide deposits. Although the variation diagrams show that magnetite compositions from various rock types have similar patterns, principal component analyses and element–element variation diagrams indicate that its composition from the same rock type in different sulfide deposits can be distinguished. This suggests that bulk-rock composition also has a strong influence on magnetite composition. Principal component analyses also show that magnetite in sulfides has a distinctive compositional signature which allows it to be a prospective pathfinder mineral for sulfide deposits in the Stollberg ore field.